Implementasi Information Retrieval System Pada Aplikasi Pencarian File Dokumen Menggunakan Metode Latent Semantic Indexing - Nur Palah; Tri Hidayati (CV. Multi Kreasi Media, 2024)
This research aims to develop a mobile-based document file search application that can help overcome the challenges faced by teachers and staff at MTs Darussalam Cisoka in searching for and retrieving stored documents on their smartphones. In the educational environment, the use of document files plays a vital role as a learning media and to fulfill various daily operational needs. However, teachers and staff often encounter difficulties in searching for or accessing these documents. Therefore, an Information Retrieval System (IRS) is implemented in the document file search application using the Latent Semantic Indexing (LSI) method. The LSI method is chosen because it can index documents based on the context and meaning contained within them, making the document search process more effective and not limited to specific keywords. By utilizing this application, teachers and staff at MTs Darussalam Cisoka can easily and efficiently search for and retrieve their stored documents on their smartphones, allowing for faster access and retrieval